Effects of oral environment on frailty: particular relevance of tongue pressure - Satake, Anna (Clin Interv Aging, 2019)
PURPOSE: Oral frailty or the loss of oral functionality can be a symptomatic precursor of overall frailty. Previous studies have suggested that decreased tongue pressure causes a decline in ingesting and swallowing function and poor nutrition. This study investigated what factor(s) contribute to tongue pressure, thereby leading to frailty. PATIENTS AND METHODS: For the purposes of the present study, 467 residents of Hirosaki city in northern Japan aged≥60 years who completed a questionnaire about frailty and underwent an intraoral assessment, which included number of teeth, presence or absence of periodontitis, tongue pressure, and oral diadochokinesis (ODK) were recruited. RESULTS: Of the 467 participants with complete data sets, frailty was identified in 13 (7.5%) of 173 males and in 34 (11.6%) of 294 females. Significantly fewer teeth, lower tongue pressure, and a reduced diadochokinetic syllable rate were more prevalent among frail than among healthy residents. Multivariable logistic regression analysis revealed that age, body mass index, number of teeth, and tongue pressure significantly contributed to frailty, whereas ODK did not. Multiple regression analysis showed that tongue pressure was positively associated with muscle index and number of teeth. CONCLUSION: The results of the present study suggest that fewer teeth and lower tongue pressure, but not ODK function, are risk factors for developing overall frailty among older residents.